MRI assessment of sacral injury location and analysis of influencing factors after high-intensity focused ultrasound ablation for patients with uterine fibroids - Zhou, Ao; Feng, Xin; Lv, Furong; Tan, Yunyue; Liu, Yuhang; Xiao, Zhibo (Frontiers in Physiology, 2025)
PurposeExploration of the location of sacral injuries following ultrasound-guided high-intensity focused ultrasound (USgHIFU) ablation for uterine fibroids and analysis of its influencing factors.MethodsA retrospective analysis was conducted on 663 patients with uterine fibroids treated by USgHIFU ablation. Patients with vertebral injuries were identified based on postoperative MRI images, with specific locations of the injuries documented. Additionally, the condition of muscle damage around the vertebral body was assessed. Patients were divided into Upper group and Lower group based on the location of vertebral injuries. Univariate and multivariate logistic regression analyses were conducted to identify the influencing factors. The χ2 test was used to explore the relationship between the location of vertebral injuries and postoperative clinical adverse events, as well as muscle damage.ResultsPostoperative MRI examinations revealed that 42.3% (281/663) of the patients experienced vertebral injuries, which were localized to the range from L5 to S5. The injuries from L5 to S2 were classified as Upper group, accounting for 45.2% (127/281), while those from S3 to S5 were classified as Lower group, accounting for 54.8% (154/281). Multivariate analysis revealed that the distance from the ventral side of the fibroid to the abdominal wall skin, uterine position, and T2WI signal intensity were positively correlated with the location of sacral injuries (p < 0.05). Additionally, the location of sacral injuries was significantly associated with the occurrence of postoperative sacrococcygeal pain (p < 0.05). 162 patients (57.6%) with sacral injury were accompanied by piriformis and gluteus maximus muscle injuries, with piriformis injury accounting for 95.06%. The location of sacral injury was significantly correlated with piriformis injury (p < 0.05).ConclusionPostoperative MRI images of some patients with uterine fibroids treated with USgHIFU ablation show vertebral and surrounding muscle injuries, mainly involving sacrum and piriformis. For those with a retroverted uterus, a large distance between the ventral side of the fibroid and the abdominal wall, or fibroids exhibiting high signals on T2-weighted images (T2WI), the location of postoperative sacral injuries tends to be more inferior. Additionally, these patients face an increased risk of concurrent piriformis injury and a higher likelihood of experiencing sacrococcygeal pain.